(untitled) (Journal of Comparative & International Higher Education, 2023)
The logics of identity structure and organize interactions on both individual and communal levels. These logics range from how we as researchers interact with our subjects, to how we make sense of contexts in which we find ourselves. This essay will further a global dialogue on researcher identity, a concern that has gained currency in recent years (Allen 2010, Mcdonald 2013, Muhammad et al 2015) by proposing the theoretical possibility of “anationality”: a disavowal of national identification as a possible subject position from which to negotiate local, regional, national, and global processes. Drawing on experienced gained while researching international students for an NGO, and later as a PhD student, both in countries in which I am marked as foreign, this chapter essay follows feminist theorizing of gender, particularly gender non-binary identities, to potentially illuminate the opportunities and limitations of undoing nationality (Butler 2004). It further highlights the importance of an anti-essentialist stance (Werbner 1997) in conducting research. Anationality is an attempt to question national categorization. As such, it productively moves the debate around the nation and nationality beyond normative, essentialistic conceptualizations.